تحليل الدور الاستراتيجي لتقانة المعلومات في منظمات الأعمال - الخفاجي نعمة عباس (Journal of Economics and Administrative Sciences, 2008)
The strategic approach had a great effect on information technology analysis which relevant to business organizations. The role was explicated, through uses of the strategic leadership for these approaches to support the strategic capabilities (powers) and its contribution to reach the advantage and superiority strategy. This paper was attempt to reveal the strategic philosophy or strategic talent mind had a big role on confrontation the strategic risk and challenges. The paper was concluded by represents a wide perspective for the information technology and its effects on organizations strategic role. The topic can be considered as a rational and reasonable contribution, in addition to the opportunist pragmatic analysis will support the strategic knowledge in the field of business administration. The strategic parlances will warrant the organization’s survival and its innovation. Ultimately there is a great necessity for information technology to the Arab business organizations.